Penguatan Literasi Rezeki Halal melalui Edukasi Hukum Ekonomi Syariah pada Komunitas Muslimah DIROSA - Kurnaemi Anita; Muhammad Nirwan Idris (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This community service program aimed to strengthen DIROSA participants’ literacy in Islamic Economic Law regarding the concept of lawful sustenance in family life. The program was conducted collaboratively for approximately two months by involving the community service team, student field assistants, and DIROSA community partners in South Galesong. The participants were DIROSA members from four villages, namely Bontokanang, Kalebentang, Kanaeng, and Bontokassi. The program employed a descriptive-evaluative approach through needs identification, program planning, DIROSA mentoring, the main lecture entitled “Lawful Sustenance, Blessed Family,” follow-up evaluation, and program sustainability strengthening. Data were collected through activity documentation, interviews, and a retrospective-response Google Form. The results showed that the lecture was positively received and relevant to the needs of Muslim women’s family guidance. A limited follow-up evaluation involving five respondents indicated strengthened understanding, with the average score increasing from 2.24 before the activity to 4.00 after the activity. The most notable improvement appeared in participants’ ability to distinguish lawful, doubtful, and avoidable sources of income. The program also continued through the handover of the DIROSA halaqah to the Muslimah Wahdah Branch of South Galesong.